119: METASTASECTOMY OR STEREOTACTIC BODY RADIATION THERAPY FOR OLIGOMETASTATIC ESOPHAGOGASTRIC CANCER: A NATIONWIDE POPULATION-BASED COHORT STUDY. (23rd April 2022) - Kroese, T; Jorritsma, N; Haj Mohammad, N; Mook, S; Ruurda, J; Verhoeven, R; Van Rossum, P; Van Laarhoven, H; Van Hillegersberg, R
Abstract: Background and aim: This nationwide population-based study analyzed the outcome of local treatment for oligometastatic esophagogastric cancer in The Netherlands. Methods: Patients with synchronous or metachronous oligometastasis (i.e. distant metastasis in 1 organ/extra-regional lymph node station) from esophagogastric cancer were eligible for inclusion from Netherlands Cancer Registry. Patients who underwent local treatment (i.e. metastasectomy or stereotactic body radiation therapy [SBRT]) for oligometastasis were included. The overall survival (OS) after diagnosing oligometastasis was determined. Independent prognostic factors for OS were analyzed using a multivariable Cox proportional hazard model. Results: Between 2015–2016, some 2, 336 eligible patients with oligometastasis were identified of whom 103 (4%) underwent local treatment for oligometastasis. This portion was higher in academic hospitals (10%) compared to non-academic hospitals with esophagogastric resections (5%) or without esophagogastric resections (3%, P  < 0.001). The 103 included patients were predominantly diagnosed with esophageal cancer (85%) with adenocarcinoma histology (80%) and with metachronous oligometastasis (59%). The oligometastasis were located in a distant organ (79%), an extra-regional lymph node station (12%), or the peritoneum (9%). Treatment for oligometastasis included metastasectomy (45%), SBRT (40%), or both (15%), and 21% of patients received additional systemic therapy. Median OS was 18.1 months (95% confidence interval [CI]: 13.9–22.7). The OS rate at 2-year was 36% and at 3-year 23%. Improved OS was independently associated with additional systemic therapy (hazard ratio [HR] 0.47, 95% CI: 0.23–0.96) and better performance scores (HR 0.55, 95% CI: 0.29–0.92). Conclusion: A minority of patients underwent local treatment for oligometastatic esophagogastric cancer, which was dependent on the type of hospital of diagnosis. Local treatment for oligometastasis resulted in a median OS of 1.5 years. Systemic therapy combined with local treatment for oligometastasis improved OS.